2021
DOI: 10.1002/ijfe.2479
|View full text |Cite
|
Sign up to set email alerts
|

The ex‐post impact of agricultural technology adoption on poverty: Evidence from north Shewa zone of Amhara region, Ethiopia

Abstract: This study investigates the impact of agricultural technology adoption on poverty reduction in north Shewa zone of Amhara region of Ethiopia in 2020. Using the selection model, this study finds that farm household's decision to adopt agricultural technologies are mainly influenced by sex of the household head, credit access, saving, extension visit, farm cooperatives and distance from market. Using an endogenous switching regression model, this study finds that adopters of agricultural technologies have higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
10
14
0
Order By: Relevance
“…Our results on poverty and the adoption of new technology are supported by the previous literature. For instance, poverty creates barriers to the adoption of agricultural technology [58,59]. Studies have reported that poverty negatively affects agricultural technology adoption; however, promoting awareness through extension and policy interventions can create improved technology, such as novel crop varieties that are available to farmers, and can facilitate their adoption, which, in turn, can reduce poverty.…”
Section: Povertymentioning
confidence: 99%
“…Our results on poverty and the adoption of new technology are supported by the previous literature. For instance, poverty creates barriers to the adoption of agricultural technology [58,59]. Studies have reported that poverty negatively affects agricultural technology adoption; however, promoting awareness through extension and policy interventions can create improved technology, such as novel crop varieties that are available to farmers, and can facilitate their adoption, which, in turn, can reduce poverty.…”
Section: Povertymentioning
confidence: 99%
“…In addition, even if agriculture is the mainstay of the economy, its contribution is declining over time, and its productivity is very low as well due to its heavy reliance on rain-fed farming, traditional farming, adverse climatic conditions, and minimal applications of farm technologies. The lower food production and productivity limits the national food availability and consumption requirements, which result in food insecurity problem in the country [ 4 ]. As a result, the daily calorie consumption in Ethiopia is below the recommended daily allowance of 2100 kcal/person/day [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past empirical studies have demonstrated that agricultural growth through improved and new agricultural technologies adoption is the most effective way to increase agricultural productivity, sustain food security and decrease poverty. The technology adoption in the sector of agriculture has greatly contributed to increased yields and improved household food security, thereby reducing household poverty ( De Janvry et al., 2000 , 2017 ; Kassie et al., 2018 ; Habtewold, 2021 ; Belay and Mengiste, 2021 ). Hence, various studies conducted around the world and in Ethiopia have suggested that agricultural technologies have the capability of reducing poverty in large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, various studies conducted around the world and in Ethiopia have suggested that agricultural technologies have the capability of reducing poverty in large scale. For example, the adoption of alternative farming technologies has been found to significantly increase yields, increase farm income, increase household consumption, improve nutrition, and generally improves household welfare ( Sebsibie et al., 2015 ; Hagos, 2016 ; Tesfaye et al., 2016 ; Alwang et al., 2017; Belete and Melak, 2018 ; Akinrinola and Adeyemo, 2018 ; Adebayo et al., 2018 ; Ahmed and Anang., 2019 ; Verkaart et al., 2019 ; Natnael, 2019 ; Legesse et al., 2019 ; Tesfay, 2020 ; Biru et al., 2020 ; Teka and Lee, 2020 ; Abewa et al., 2020 ; Ayenew et al., 2020 ; Shita et al., 2020 ; Belay and Mengiste, 2021 ; Habtewold, 2021 ; Wordofa et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation